Free mass health check-up at gpm lateri congregation - Nanlohy, Wildia; Fajar, Harianti; Corputty, Lintje Sintje; Latuamury, Sitti R (Journal of Evidence-Based Community Health, 2025)
According to the World Health Organization (WHO), health is a state of physical, mental, and social well-being and not merely the absence of disease or weakness. Meanwhile, according to Health Law No. 36 of 2009, health is a state of physical, mental, spiritual and social health that enables everyone to live productively socially and economically. The activity begins with registration for those who will seek treatment and anamnesis and blood measurements of patients are carried out by health workers and counseling that is individual depending on the disease suffered. After being examined, a prescription will be given for either injections or oral medication. This activity ended at around 13.45 WIT. Of the 48 patients who received treatment at GPM Lateri, 8 people suffered from rheumatism, 12 people suffered from acute respiratory infections, 5 people with gastrointestinal disorders, 23 people suffered from hypertension. 20 of the patients were women and 28 were men.